Mechanism to Reduce the Porosity during Argon Arc Welding of Aluminum Alloys by Changing the Arc Angle - Senchang Chen; Yanhui Chi; Ping Zhang; Yusheng Shi (Metals, 2020)
A mechanism to reduce the porosity by changing the arc angle during aluminum alloy welding was studied. Industrial computed tomography was used to scan the welds with different arc angles, and the scanned model was processed by a specific software package to obtain the digital size and position of weld pores. The forces acting on the pores in the molten pool explained the test results that the number of pores decreases and the average size increases. As the inclination angle of the arc increased, the vertical component that prevented the bubble from rising decreased, and the horizontal component that pushed the molten metal flow and promoted the nucleation and growth of the bubbles increased. A horizontal movement during the droplet transition as the arc inclination was produced, which was conducive to the growth and overflow of bubbles. The theoretical analysis and temperature field measured by a far-infrared with different torch angle showed that when the arc was tilted from 0, the shape of the molten pool changed from the circle to the ellipse. The long axis of the ellipse increased as the bevel angle of the arc increased. This showed that the molten metal existed a longer time for the bubbles to escape from the molten pool when the angle of the arc increased. The paper provides fundamental insights into a mechanism for porosity reduction during the welding of Al alloys.